The Use of Technologies in the Formation of Critical Thinking in Schoolchildren as a Means of Personal Self-Development - M. Abdukhalikova (Genius Publishing Group, 2023)
The article deals with the problems of using interactive methods and their role in the formation of critical thinking in schoolchildren as a means of personal self-development. Also, the introduction of technology for the development of students’ critical thinking in the classroom was discussed as well in the article
Keywords: information technology; technologies; development; interactive methods